2021
DOI: 10.3389/fpls.2021.675227
|View full text |Cite
|
Sign up to set email alerts
|

Homologs of Circadian Clock Proteins Impact the Metabolic Switch Between Light and Dark Growth in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: The putative circadian clock system of the facultative heterotrophic cyanobacterial strain Synechocystis sp. PCC 6803 comprises the following three Kai-based systems: a KaiABC-based potential oscillator that is linked to the SasA-RpaA two-component output pathway and two additional KaiBC systems without a cognate KaiA component. Mutants lacking the genes encoding the KaiAB1C1 components or the response regulator RpaA show reduced growth in light/dark cycles and do not show heterotrophic growth in the dark. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Comparison of the growth under different conditions of mutant strains to the WT, revealed that the application of glucose in light-dark cycles had the strongest effect on the growth of rne (5p). A similar phenotype has been described for Synechocystis mutants lacking genes encoding components of the circadian clock [ 96 ], the sRNA Ncr0700/PmgR1 [ 75 ]; or alternative sigma factors [ 97 ], regulatory factors which all target a large number of genes. However, due to the large variety of transcript types and segments affected by RNase E, we are not able to relate growth defects with any specific targets.…”
Section: Discussionmentioning
confidence: 53%
“…Comparison of the growth under different conditions of mutant strains to the WT, revealed that the application of glucose in light-dark cycles had the strongest effect on the growth of rne (5p). A similar phenotype has been described for Synechocystis mutants lacking genes encoding components of the circadian clock [ 96 ], the sRNA Ncr0700/PmgR1 [ 75 ]; or alternative sigma factors [ 97 ], regulatory factors which all target a large number of genes. However, due to the large variety of transcript types and segments affected by RNase E, we are not able to relate growth defects with any specific targets.…”
Section: Discussionmentioning
confidence: 53%
“…3 ). Furthermore, elevated ROS and glutathione levels is another aspect of the metabolic crisis, which the mutants undergo in diurnal growth and which, besides others, ultimately leads to cell death, similar to what observed in the mutant of the circadian clock regulator, RpaA (Diamond et al 2017, Scheurer et al 2021). Notably, our proteomics dataset revealed a slight reduction of RpaA ( slr0115 ) levels in Δ dacA ( Supplemental Table S3 ).…”
Section: Resultsmentioning
confidence: 70%
“…To find these limits of E 13 C determination, all positional aspartic acid standards were combined equally and then isotopically diluted by natural aspartic acid in different proportions (Table S1). Injections of 1.25 ng up to 250 ng of each mixture were analyzed to cover the abundance-range of our analyses in agreement with the expected biological variation 28, 39 . Most fragment ions showed small absolute value deviations from expected E 13 C when 12.5 ng or more were injected ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 79%